THE EFFECTS OF A SCHOOL BAG LOAD CARRIAGE ON GAIT KINEMATICS IN CHILDREN: A SCHOOL-BASED STUDY (Kinesiology, 2025)
The main purpose of this study was to explore the impact of carrying a school bag on spatiotemporal gait parameters in a sample of primary school children. Two-hundred and twenty-one children (124 girls and 97 boys), aged 9.5±2.1 years, were randomly selected from three primary schools in the city of Brno, Czech Republic. Gait analysis without and with the school bag load carriage was performed using the Zebris pressure platform. The software generated the data for spatial (foot rotation, step length, stride length and step width) and temporal (step time, stride time, cadence and gait speed) gait parameters. The mean school bag weight was 4.86±1.21 kg. Repeated measures ANCOVA adjusted for sex and age showed that carrying a school bag resulted in a higher external left foot (F1,220=8.390, p